Percutaneous drainage of a localized biatrial haematoma causing regional tamponade in a patient with prior coronary artery bypass graft surgery: a case report. Issue 8 (28th July 2022) - Achim, Alexandru; Toia, Damien; Leibundgut, Gregor
Abstract: Background: Regional cardiac tamponade presented as posterior extrapericardial haematomas compressing both atria, with cardiogenic obstructive shock due to inflow abolition is a rare cause of post-percutaneous coronary intervention vascular collapse. Case summary: We present such a case where computed tomography-guided anterior pericardiocentesis decompressed the atria and restored cardiac output. Discussion: Prior coronary artery bypass grafting should not be considered protective from cardiac tamponade in patients in whom perforation occurs, because loculated effusions can develop beneath adhesions of the pericardium and compress various cardiac structures (such as the left atrium or the right ventricle); they appear several hours after the intervention and cause atypical haemodynamic manifestations.